Decision Support System for Determining the Best Foreman Using the Simple Additive Weighting (SAW) Method - Wiraguna, Rizky; Irfan Sarif , Muhammad (Cattleya Darmaya Fortuna, 2024)
Universal Gloves is a company engaged in the production of rubber gloves in the city of Medan. The increasing number of foremen working in this company makes the diversity of foremen even more complex so that it is difficult to choose the best foreman. Therefore, it is necessary to develop a decision support system as an alternative solution to increase efficiency and effectiveness in the selection and quality of determining the best foreman. This decision support system uses the SAW (Simple Additive Weighting) method based on predetermined criteria and weights. The criteria used as indicators are Discipline, Initiative, Achievement, Cooperation, Order, Performance, and Social. The SAW method was chosen because it was able to select the best alternative from a number of alternatives. This research was carried out by looking for weights on each attribute, then ranking was carried out to determine the best foreman. The results of this study are in the form of a decision support application that can recommend the best foreman at PT. Universal Gloves.